Pertanggungjawaban Hukum Atas Pencemaran Mikroplastik di teluk Jakarta - Rayi Kharisma Rajib; Noor Hamzah Syihabuddin; Anggia Khalidi Sriadiputra (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Microplastic pollution in Jakarta Bay has become an increasingly complex environmental issue, posing serious threats to marine ecosystems and human health. Microplastics originating from domestic waste, industrial activities, and urban runoff are persistent and difficult to degrade, allowing them to accumulate within the food chain. This study aims to analyze the forms of legal liability for microplastic pollution and to identify the challenges in its law enforcement in Indonesia. This research employs a normative legal method using statutory and conceptual approaches. The results indicate that the regulation of microplastic pollution within Indonesian environmental law remains general and lacks specific provisions addressing this type of pollution. This condition leads to weak legal certainty in determining liability for polluters. Furthermore, law enforcement faces several obstacles, including difficulties in scientific proof, the complexity of pollution sources, and weak institutional coordination and supervision. From an environmental law perspective, legal liability for microplastic pollution should be implemented through the principles of strict liability and the polluter pays principle. However, the application of these principles remains suboptimal in practice. Therefore, it is necessary to reform existing regulations, strengthen law enforcement capacity, and improve waste management systems to enhance the effectiveness of legal accountability for microplastic pollution in Jakarta Bay.